Recommendations without action: criticism of the Javanese Language Congress and the Javanese Cultural Congress in Indonesia - Dhoni Zustiyantoro (Cogent Arts & Humanities)
This paper criticizes the Javanese Language Congress and the Javanese Cultural Congress, which are held every five years in Indonesia, but the results are insufficient to preserve and develop the Javanese language and culture. The Javanese people’s language and culture must be preserved because they hold the values of wisdom and life guidelines that become character. That includes being internalized into the school curriculum. All problems are ironic because Congress spent such a large state budget. Even though it has the largest population, academic studies show that the Javanese language and culture are vulnerable due to globalisation and popular culture among teenagers. This paper argues that the two congresses need to be more progressive so that the meeting results can advance the Javanese language and culture. By highlighting the issue of recommendations without tangible actions, this study underscores the importance of redefining the purpose and structure of these congresses to ensure that they serve as platforms for discourse and effective implementation. The findings emphasize the significance of aligning stakeholders’ efforts to drive meaningful change, fostering greater collaboration between government bodies, educational institutions, cultural communities, and individuals invested in Javanese language and culture. Moreover, the study’s insights can inform the development of comprehensive implementation strategies, inspiring future research to delve deeper into the societal impact of congresses and contributing to more proactive and impactful preservation and promotion of Javanese linguistic and cultural heritage.